2021
DOI: 10.3389/fnhum.2021.763821
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological, but Not Behavioral, Indicator of Working Memory Capacity Predicts Video Game Proficiency

Abstract: Visual working memory (VWM) is the ability to actively maintain visual information over short periods of time and is strongly related to global fluid intelligence and overall cognitive ability. In our study, we used two indices of visual working memory capacity: the behavioral estimate of capacity (K) and contralateral delay activity (CDA) in order to check whether training in a Real-Time Strategy (RTS) video game StarCraft II can influence the VWM capacity measured by the change detection task. We also asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Behavioral results obtained from the current study were independently analyzed (together with the CDA potential, which also belongs to neurophysiological indicators of VWM) in one of previously published articles prepared by our lab. 13 As our previous investigation found that the behavioral indicators were not predictive in terms of in-game achievements and this property has already been described in detail, this time they were omitted in advance.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Behavioral results obtained from the current study were independently analyzed (together with the CDA potential, which also belongs to neurophysiological indicators of VWM) in one of previously published articles prepared by our lab. 13 As our previous investigation found that the behavioral indicators were not predictive in terms of in-game achievements and this property has already been described in detail, this time they were omitted in advance.…”
Section: Discussionmentioning
confidence: 92%
“…As presented results constitute only a part of actual data that was collected for a bigger-scaled project, detailed analysis for behavioral data and its interpretation in relation to EEG and telemetric results can be found in a paper by Jakubowska and colleagues. 13 For electrophysiological data, the mean power for theta (4-8 Hz) and alpha (8-12 Hz) frequency bands were the outcome variables. We decided to calculate power spectral densities using the full epoch time window (up to 1490 ms after the stimuli), from single electrodes: electrode Pz for alpha-band and electrode FCz for theta-band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term differs from the conception of short-term memory, which refers "to the simple temporary storage of information, in contrast to WM, which implies a combination of storage and manipulation" (BADDELEY, 2012, p. 4). As a psychometric construct, WM influences performance in highly demanding cognitive tasks such as learning novel words (GRAY et al, 2022), long-term memory encoding (FORSBERG et al, 2021;MELROSE et al, 2020), mathematical problem-solving (SWANSON; ARIZMENDI; LI, 2021), and video game acquisition (JAKUBOWSKA et al, 2021), among others.…”
Section: Introductionmentioning
confidence: 99%